The Montreal Protocol’s multilateral fund: an environmental and economic success - Tieszen, Brett (Kansas State University, 2010)
Although the ozone layer is vital to life on Earth, as a common resource it has been the subject of rational exploitation. With ozone depletion a global (rather than merely regional) problem, measures to address it have necessarily been international efforts. The international treaty that addressed ozone depletion, the Montreal Protocol (with its subsequent amendments), has widely been hailed as a success. However, the triumphs of the Montreal Protocol are inseparable from its Multilateral Fund, whose creation was a prerequisite for developing nations, including juggernauts China and India, to ratify the Protocol. Since its inception the Fund has supplied over $2.5 billion to initiatives that support the phase-out of ozone-depleting chemicals in developing nations. These projects have increasingly employed market mechanisms to achieve efficient results, and have generated positive profits for participating firms. Funded initiatives have included upgrading capital, educating maintenance workers, production buyouts, public awareness, and institutional strengthening. Aside from ensuring the success of the overall Protocol, this last item will likely be the Multilateral Fund’s most enduring legacy, as inherent shortcomings of the Fund have largely been attributed to its status as a pioneering financial mechanism. The Multilateral Fund has broken new ground in international environmental regulation and shown that success on ecological issues is indeed possible at the global level, leading many to hope that the Fund will serve as a model for future mechanisms to address climate change. While the more complex chemistry and economics of climate change make such a ready duplication of the Multilateral Fund’s success unlikely, the Fund’s role in strengthening institutions that address ecological concerns has undoubtedly smoothed the way for future international environmental action.
Keywords: Montreal Protocol; Multilateral Fund; Ozone; Economics, General (0501)